Predictive value of liver and spleen stiffness in advanced alcoholic cirrhosis with refractory ascites - Lindner, Franziska; Mühlberg, Reinhard; Wiegand, Johannes; Tröltzsch, Michael; Hoffmeister, Albrecht; Keim, Volker; Karlas, Thomas (Zeitschrift für Gastroenterologie, 2018)
Background Recurrent ascitic decompensation is a frequent complication of advanced alcoholic liver disease. Ascites can be controlled by transjugular intrahepatic portosystemic shunt (TIPS) implantation, but specific pre-procedural outcome predictors are not well established. Liver and spleen stiffness measurement (LSM, SSM) correlate with outcome of compensated liver disease, but data for decompensated cirrhosis disease are scarce. Therefore, the predictive value of LSM and SSM was evaluated in patients with refractory ascites treated with TIPS insertion or receiving conservative therapy.Material and Methods Patients with alcoholic liver cirrhosis and recurrent or refractory ascites were stratified according to TIPS eligibility. LSM was prospectively assessed by transient elastography (TE, XL probe) and point shear wave elastography (pSWE). pSWE was also used for SSM. The primary study endpoint was transplant-free survival after 12 months. In addition, correlation of LSM and SSM with TIPS complications was analyzed.Results 43 patients (16 % female, age 55.5 [28.6 – 79.6] years) were recruited, n = 20 underwent TIPS and n = 23 were treated with repeated paracenteses only. 15 patients died and five underwent liver transplantation during follow-up. LSM and SSM at baseline did not predict the patients’ outcome in the TIPS cohort and in patients with conservative therapy. SSM was increased in two cases with spontaneous TIPS occlusion and declined after revision.Conclusion LSM and SSM cannot be recommended for risk stratification in cirrhotic patients with refractory ascites. SSM may be useful in monitoring TIPS function during follow-up.
Keywords: transient elastography (TE); point shear wave elastography (pSWE); refractory ascites; transjugular intrahepatic portosystemic shunt (TIPS); decompensated cirrhosis; spleen stiffness